Irregular Applications: From Architectures to Algorithms [Guest editors' introduction]. - Tumeo, Antonino; Feo, John (Computer (00189162), 2015)
Irregular applications present unpredictable memory-access patterns, data-dependent control flow, and fine-grained data transfers. Only a holistic view spanning all layers of the hardware and software stack can provide effective solutions to address these challenges.